2021
DOI: 10.1111/jocn.15819
|View full text |Cite
|
Sign up to set email alerts
|

Rotating between day and night shifts: Factors influencing sleep patterns of hospital nurses

Abstract: Aims and Objectives: This study aimed to investigate sleep patterns of hospital nurses using a wearable electronic device and determine the influence of rotating day and night shifts and lifestyle factors on their sleep efficiency.Background: Nurses working in shifts are vulnerable to sleep disturbances. However, little is known about the influence of rotating day and night shift schedules and healthy lifestyle on nurses' daily sleep patterns. Design: Descriptive correlational design.Methods: Thirty-two hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Particularly, night shifts were related to late sleep onset, rather than sleep maintenance or early wakening problems. Our results are in line with one previous study (59), which found significantly longer sleep latency in shift-work nurses. Moreover, we found night shifts were related to depressed mood and appetite change.…”
Section: Discussionsupporting
confidence: 94%
“…Particularly, night shifts were related to late sleep onset, rather than sleep maintenance or early wakening problems. Our results are in line with one previous study (59), which found significantly longer sleep latency in shift-work nurses. Moreover, we found night shifts were related to depressed mood and appetite change.…”
Section: Discussionsupporting
confidence: 94%
“…For example, Chang and Peng reported that nurses with rotating or irregular shifts tend to suffer more musculoskeletal disorders than those with fixed shifts (Chang & Peng, 2021). In addition, the rotating shift has been associated with higher perceived stress, lower sleep duration and quality, higher levels of fatigue, the more gastrointestinal problem such as heartburn and stomach‐ache, and burnout (Chang & Wang, 2021; Chiang et al, 2022; Kim et al, 2017; Shahriari et al, 2014; Shin & Kim, 2021).…”
Section: Introductionmentioning
confidence: 99%